2020
DOI: 10.7717/peerj.10335
|View full text |Cite
|
Sign up to set email alerts
|

The rs78378222 prevalence and the copy loss of the protective allele A in the tumor tissue of diffuse large B-cell lymphoma

Abstract: Background Rare single nucleotide polymorphisms (SNPs) are likely to be a crucial genetic factor for human diseases, including cancer. rs78378222 is rare SNP in 3′-untranslated region (UTR) of TP53 gene leading to disturbance of 3′-end mRNA processing. The frequency of rs78378222 varies in several studied populations. The meta-analysis of 34 genome-wide association studies indicated that rs78378222 was significantly associated with an increased risk of cancer overall. Bioinformatic analysis indicates that soma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
0
4
1
Order By: Relevance
“…In contrast with our findings in LUAD tumors, recent studies have identified that, regardless of tumor type, rs78378222[C] is more frequent in tumors with no somatic-coding pathogenic TP53 variants, i.e. WT TP53 tumors ( Voropaeva et al ., 2020 ; Zhang et al , 2021 ). The rs78378222[C] minor allele was not associated with lung cancer (not specified distribution of histological types) in a case series from the USA ( Guan et al ., 2013 ),…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast with our findings in LUAD tumors, recent studies have identified that, regardless of tumor type, rs78378222[C] is more frequent in tumors with no somatic-coding pathogenic TP53 variants, i.e. WT TP53 tumors ( Voropaeva et al ., 2020 ; Zhang et al , 2021 ). The rs78378222[C] minor allele was not associated with lung cancer (not specified distribution of histological types) in a case series from the USA ( Guan et al ., 2013 ),…”
Section: Discussioncontrasting
confidence: 99%
“…The results of the current study must be interpreted in the context of the following limitations: (1) although our overall sample size is more than 800 individuals and a recent study in the Russian population described a very high somatic frequency of rs78378222[C] carriers analyzing only 136 cases of a lymphoma subtype (11/136, 8.1 %) ( Voropaeva et al ., 2020 ), our cancer cohorts actually have a relatively small number of patients for analysis of a rare variant in ULM (n = 41) and SARC (n = 188) study groups; (2) LUAD tumor samples were obtained from a retrospective study and de-identified for use in the current study, hindering the complete clinical characterization of this case series regarding the ethnic ancestry, cancer family history, and histological subtype; (3) the other two positive LUAD cases whose NGS analyses were not performed due to limitations in sample availability could be important for more robust interpretations of LUAD samples with TP53 variants co-occurring with rs78378222[C].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…This variant has been implicated in several studies as a low-penetrance risk factor in LFS and cancer. 52 , 53 , 54 In ClinVar, this variant has been reported in the context of LFS twice (RCV000412103.10) and in the context of hereditary cancer-predisposing syndrome twice (RCV000492363.7). Under both diseases, there is both a benign/likely benign and a VOUS classification.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the current Special Issue on medical genomics shows that bioinformatics tools for the systems analysis of human diseases are in high demand, as could be seen from recently published post-conference papers [28,29]. The outputs of disease model analysis come in the form of sets of genes and protein markers which represent a particular interest to medical practitioners [30]. The guest editors are happy to announce that the next Special Issue topic at MDPI IJMS will be on medical genomics (https://www.mdpi.com/journal/ ijms/special_issues/Medical_Genetics_2021, accessed on 25 August 2021).…”
mentioning
confidence: 99%